Relearning to Fixate as an Adult with Strabismic Amblyopia: Supportive Evidence of Neuroplasticity. - Yutaka Maki; Coates, Russell S. (Optometry & Visual Performance, 2019)
Background: Neuroplasticity is the basis for accepting adult strabismic/amblyopic patients into vision therapy. Although the patient's age has a large impact on the prognosis, it is only one of the deciding factors. Patient goals/motivation, fixation, correspondence, magnitude and frequency of strabismus, suppression, degree of fusion, etc. also have a significant impact on the patient's prognosis. Case Report: A 34-year-old Caucasian female with long-standing strabismus and amblyopia presented with a goal to improve her vision OS. Best-corrected visual acuities (BCVA) were 20/20 OD, 20/100-2 OS at distance and 20/20 OD, 20/80-2 OS at near. Other pertinent findings included: 4-6 PD constant left esotropia, anomalous correspondence at near, steady central fixation OD, steady 1.5 PD nasal eccentric fixation OS, central suppression OS, flat fusion at 40 cm and 1 m, simultaneous perception (eso) at 2 m with partial suppression OS, and suppression OS at 3m. The patient was informed of a guarded prognosis, and a tensession, trial-basis course of vision therapy was initiated. The patient's degree of eccentric fixation changed to unsteady 0.5 PD nasal eccentric fixation OS after ten weeks. The patient self-discontinued the therapy program after 18 sessions (due to job constraints) with a final BCVA of 20/50-1 OS without visual symptoms. Conclusion: The significant improvement achieved in the patient's visual acuity OS was evidence of neuroplasticity in adult patients. The most probable reason for the improvement in visual acuity was the improvement of monocular fixation OS. In addition, strong motivation and compliance with vision therapy homework led to success.